ANALISIS PERENCANAAN KEBUTUHAN BAHAN BAKU MEUBEL PADA CV. KARYA HARAPAN WATU CI’E DI KECAMATAN POCORANAKA TIMUR, KABUPATEN MANGGARAI TIMUR - Wuleng, Filomena Wiwin Wai; Banda, Falentina Lucia; Soleiman, Iriany Dewi (Program Studi Akuntansi Universitas Flores, 2022)
The formulation of this research is how is the planning of furniture production at CV. Karya Harapan Watu Ci'e?. The goal to be achieved in this study is to analyze furniture production planning at CV. by Harapan Watu Ci'e?. This research uses a type of qualitative research. The location of this research is at CV. Karya Harapan Watu Ci'e, East Manggarai Regency. Data collection techniques are Observation, Interview, Documentation Study, and Literature Study. Based on the results of research on the company CV. Harapan Watu Ci'e's work can be said to be not good because of the problem of insufficient supply of raw materials, when customer demand is soaring. This has been proven by CV. Karya Harapan Watu Ci'e experienced fluctuations. In 2019-2021 it has decreased. In addition, the system applied to CV. Harapan Watu Ci'e's work is still familial and conventional, carried out by subjective judgment without being based on precise calculations. Requests made by management are also subjective and based on experience in previous periods. Therefore, the company must look again at the raw material inventory planning to be produced, so that when producing it, it does not experience shortages and excesses.